(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The financial sector is considered to be the vital component of an economy. Financialinstitutions play a distinctive role in verifying the transfer of this essential resource from its point of originto the sectors of the economy with the greatest potential for growth. The function holds a distinctiveimportance in developing nations owing to the restricted funding sources and notable variability in projectreturns. The matter is exacerbated by the nascent state of the capital markets, impeding the ability ofsavers to engage in direct investments in high-yielding enterprises. The present study posits that thesustainable growth of the banking sector in India and the prevention of periodic spells of nonperformingassets can only be achieved through private ownership of banks. While it is possible in theory torestructure Public Sector Banks (PSBs) while maintaining government ownership, the bureaucraticsystem in India has not yet accomplished this and is improbable to achieve it in the future. Hence, it isimperative to focus on advocating for the privatization of Public Sector Banks (PSBs) and delineating thefeasible pathways leading to it. Thus, this is the objective that has been established for the presentinvestigation.